Efektivitas Satgas PPKS Perguruan Tinggi dalam Melindungi Korban Kekerasan Seksual : Studi Analisis Satgas PPKS Untirta (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Sexual violence is a critical issue in Indonesia, especially within the context of higher education. Various studies and statistical data indicate a growing number of cases, including incidents in university settings that often go unreported due to social stigma and lack of support systems. This research aims to evaluate the effectiveness of the Sexual Violence Prevention and Handling Task Force (SATGAS PPKS) at Sultan Ageng Tirtayasa University in providing protection for victims. The method used is empirical juridical, combining primary data through interviews with SATGAS PPKS members and secondary data in the form of laws, academic literature, and official reports. The research adopts a qualitative descriptive analysis technique to assess how far the SATGAS PPKS applies principles of victimology and routine activity theory to support victims and reduce the opportunity for sexual violence in campus environments.